Physiological Acute Response to High-Intensity Intermittent and Moderate-Intensity Continuous 5 km Running Performance: Implications for Training Prescription - Cabral-Santos, Carolina [UNESP]; Gerosa-Neto, José [UNESP]; Inoue, Daniela S. [UNESP]; Rossi, Fabrício E. [UNESP]; Cholewa, Jason M.; Campos, Eduardo Z.; Panissa, Valéria L. G.; Lira, Fábio S. [UNESP] (De Gruyter, 2017)
The aim of this study was to investigate the physiological responses to moderate-intensity continuous and high-intensity intermittent exercise. Twelve physically active male subjects were recruited and completed a 5-km run on a treadmill in two experimental sessions in randomized order: continuously (70% sVO2max) and intermittently (1:1 min at sVO2max). Oxygen uptake, excess post-exercise oxygen consumption, lactate concentration, heart rate and rating of perceived exertion data were recorded during and after each session. The lactate levels exhibited higher values immediately post-exercise than at rest (High-Intensity: 1.43 ± 0.25 to 7.36 ± 2.78; Moderate-Intensity: 1.64 ± 1.01 to 4.05 ± 1.52 mmol·L-1, p = 0.0004), but High-Intensity promoted higher values (p = 0.001) than Moderate-Intensity. There was a difference across time on oxygen uptake at all moments tested in both groups (High-Intensity: 100.19 ± 8.15L; Moderate-Intensity: 88.35 ± 11.46, p < 0.001). Both exercise conditions promoted increases in excess postexercise oxygen consumption (High-Intensity: 6.61 ± 1.85 L; Moderate-Intensity: 5.32 ± 2.39 L, p < 0.005), but higher values were observed in the High-Intensity exercise protocol. High-Intensity was more effective at modifying the heart rate and rating of perceived exertion (High-Intensity: 183 ± 12.54 and 19; Moderate-Intensity: 172 ± 8.5 and 16, respectively, p < 0.05). In conclusion, over the same distance, Moderate-Intensity and High-Intensity exercise exhibited different lactate concentrations, heart rate and rating of perceived exertion. As expected, the metabolic contribution also differed, and High-Intensity induced higher energy expenditure, however, the total duration of the session may have to be taken into account. Moreover, when following moderate-intensity training, the percentage of sVO2max and the anaerobic threshold might influence exercise and training responses.
Keywords: acute exercise; energy expenditure; excess post-exercise oxygen uptake; high intensity intermittent exercise; lactate concentration; physiologic responses